Promoting talent development in honours: The Honours Experience - Pierre van Eijl; Albert Pilot; Vincent Gelink; Ninib Dibo (Journal of the European Honors Council, 2017)
In recent years many honours programmes were introduced at universities and colleges in the Netherlands (Van Eijl, Pilot & Wolfensberger, 2010). An important goal of these programmes is to stimulate students to more fully develop their talents. To get more insight in the process of talent development from the perspective of honours students, we started a project. Forty honours students and honours alumni from eleven different universities and eight of their teachers were interviewed about the development of their talents, why they participated in an honours programme and what their experiences were in those programmes (Van Eijl & Pilot, 2016). These interviews gave an in-depth picture of students’ honours experiences and thereby gave insight into the process of talent development. This process is represented by the Circle of Talent Development. In the second part of this paper (step 9b of the Circle) we focus on the use of honours as laboratory for 21st century skills and the dilemma of teachers between “control and letting go” are discussed.